Digitalization of accounting and analytical support for the management of small business entities - Myskin, Yurii; Izmailov , Yaroslav; Kiselova, Alona (Ways to Improve Construction Efficiency, 2025)
The digital transformation of the economy has fundamentally changed the mechanisms of information generation, processing, and utilization in enterprise management systems. Small business entities, being the most dynamic component of the national economy, face the urgent necessity of integrating digital technologies into their accounting and analytical systems. The evolution of accounting from a traditional system of transaction recording to an integrated analytical tool for decision-making underscores the growing role of digitalization in ensuring information transparency, reliability, and timeliness. However, the process of digital transformation in accounting practice remains uneven, constrained by methodological, technological, and organizational challenges. The purpose of the article is to investigate the theoretical and methodological foundations of digitalizing the accounting and analytical support of management in small business entities, to identify the key trends, problems, and prospects for improving their information systems in the context of digital transformation. The research applies general scientific and special methods, including dialectical, analytical, comparative, and synthesis methods. The dialectical method is used to study the development of accounting theory under the influence of digitalization; the analytical and comparative methods – to assess the differences in national and international approaches to implementing digital accounting technologies; and the synthesis method – to formulate conceptual conclusions and practical recommendations for enhancing accounting and analytical systems of management. The study reveals that digitalization of accounting and analytical support enables a qualitative transformation of information flows in small business management. The use of cloud technologies, accounting automation, and integrated analytical platforms contributes to increasing the operational efficiency and reliability of financial data. The implementation of digital tools facilitates real-time data processing, enhances decision-making, and supports managerial control based on predictive analytics. Nevertheless, the study highlights key limitations, including insufficient digital competence among accountants, the lack of unified methodological standards for digital accounting processes, and the cybersecurity risks associated with cloud-based data storage. The findings confirm that the digitalization of accounting functions should be approached as a complex organizational and technological process that requires synchronization between regulatory, methodological, and infrastructural dimensions. Digitalization of accounting and analytical support for small business management represents a decisive factor in increasing competitiveness and sustainability under modern economic conditions. The study substantiates the need to develop a coherent digital accounting framework that integrates cloud computing, artificial intelligence, and big data analytics to ensure the relevance and integrity of management information.